Methods of expanding an abridged life tables: Comparison between two methods - Ibrahim, R.I.; Siri, Z. (Penerbit Universiti Kebangsaan Malaysia, 2011)
A question of interest in the demografic and actuarial fields is the estimation of the complete sets of q(x)-values when the data are given in age groups. This study presents two techniques of expanding an abridged life table to a complete ones. The two expansion techniques used in the study are King's Osculatory Interpolation and Heligman-Pollard model. This work evaluated and compared the performance of King's Osculatory Interpolation and Heligman-Pollard model. For that purpose, empirical data sets on abridged life tables for Malaysian populations for the period of 1991, 1995 and 1999 for both gender were collected. Then each of the expanding techniques considered was applied to these abridged data sets. The complete sets of q(x)-values obtained from these two techniques were then used to produce the estimated abridged ones. These results were then compared with the actual values published in the abridged tables.